(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2019)
The deposit “El Domo” is located in the foothills of the western rift of Ecuador, 13 km to Las Naves, province of Ecuador Bolívar. It is formed by rocks corresponding to the arc of volcanic islands of the Fm. Macuchi Paleocene-Eocene age, it is characterized for being a deposit Volcanogenic Massive Sulphide type Kuroko. The present investigation was oriented in the study of data obtained in 30 drillholes to perform a Geological – Geochemical characterization that includes the relationship between lithologies, mineralization, laboratory results for 12 elements; the main ones of metal ore Au, Ag, Cu, Pb, Zn and the tracer elements As, Ba, Cd, Hg, Mn, Sb, Sr; for the geological understanding of the site, 10 East-West sections were elaborated to create a 3D geological model of how they are distributed lithostratigraphically from the beginning of the system; to the chemical elements were subjected to geostatistical treatment to obtain the background, threshold, subanomaly, anomalies and geochemical profiles, the correlation of the elements helped to identify the events of hydrothermal pulsation when Massive Sulphide was formed; the deposit originated during a significant tectonic event caused by submarine volcanism that began with the eruption of an acidic magmatic complex (Lower Acid Unit) later this first event served as a feeding zone for the passage and deposition of the Massive Sulphide followed by a third tuff sedimentation event (Upper Tuff Unit).